Measurement of B (t → W b) / B (t → W q) at sqrt(s) = 1.96 TeV - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Agelou, M; Agram, J; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; et al. (2006)
We present the measurement of R = B (t → W b) / B (t → W q) in p over(p, ̄) collisions at sqrt(s) = 1.96 TeV, using 230 pb-1 of data collected by the DØ experiment at the Fermilab Tevatron Collider. We fit simultaneously R and the number (Nt over(t, ̄)) of selected top quark pairs (t over(t, ̄)), to the number of identified b-quark jets in events with one electron or one muon, three or more jets, and high transverse energy imbalance. To improve sensitivity, kinematical properties of events with no identified b-quark jets are included in the fit. We measure R = 1.03-0.17+0.19 (stat + syst), in good agreement with the standard model. We set lower limits of R > 0.61 and | Vt b | > 0.78 at 95% confidence level. © 2006 Elsevier B.V. All rights reserved.